Local Impacts of Religious Discourses on Rights to Express Same-Sex Sexual Desires in Peri-Urban Rio de Janeiro. - García, Jonathan; Laboy, Miguel Muñoz; de Almeida, Vagner; Parker, Richard (Sexuality research & social policy : journal of NSRC : SR & SP, 2009)
This article reports on a study that examined how religious discourses of inclusion and exclusion-in Roman Catholic, evangelical Protestant, and Afro-Brazilian religious traditions-affected people's rights to express same-sex sexual desires, behaviors, and identities in the socioeconomically marginalized urban periphery of Rio de Janeiro, Brazil. Using extended ethnographic observation of institutions and religious events over a period of 2 years, the authors identified how sexual rights were constructed within religious discourses and conducted ethnographic interviews with 45 religious leaders. In the low-income and violent urban periphery of Rio de Janeiro, religious leaders and institutions play key roles in molding community inclusion and exclusion. A comparison of the 3 major religious denominations shows a diversity of discourses about same-sex sexual desires and their impacts on community formation.